Astral microtubules control redistribution of dynein at the cell cortex to facilitate spindle positioning - Tame, Mihoko A (Landes Bioscience, 2014)
Cytoplasmic dynein is recruited to the cell cortex in early mitosis, where it can generate pulling forces on astral microtubules to position the mitotic spindle. Recent work has shown that dynein displays a dynamic asymmetric cortical localization, and that dynein recruitment is negatively regulated by spindle pole-proximity. This results in oscillating dynein recruitment to opposite sides of the cortex to center the mitotic spindle. However, although the centrosome-derived signal that promotes displacement of dynein has been identified, it is currently unknown how dynein is re-recruited to the cortex once it has been displaced. Here we show that re-recruitment of cortical dynein requires astral microtubules. We find that microtubules are necessary for the sustained localized enrichment of dynein at the cortex. Furthermore, we show that stabilization of astral microtubules causes spindle misorientation, followed by mispositioning of dynein at the cortex. Thus, our results demonstrate the importance of astral microtubules in the dynamic regulation of cortical dynein recruitment in mitosis.